Analyze Of Process Parameter Variance In 19nm Wsi2/Tio2 NMOS Device Using 2k-Factorial Design - Salehuddin, F.; Roslan, Ameer F.; Zailan, A.E.; Kaharudin, K.E.; Zain, A.S.M.; A.H., Afifah Maheran; Hanim, A.R.; Hazura, H.; Idris, S.K.; Mohd Saad, Wira Hidayat (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This project investigates and analyzes the impact of process parameter variance on the drive current (ION) and leakage current (IOFF) for 19nm WSi2/TiO2 NMOS device using 2k-factorial design. The four process parameter, namely halo implant dose, halo implant energy, source/drain (S/D) implant dose and S/D implant energy will be investigated and adjusted to improve the results. The simulated of the device was performed by using ATHENA module. Meanwhile the electrical characterization of the device was implemented by using ATLAS module. These two modules will be combined with 2kfactorial to aid design and optimize the process parameters. The most effective process parameter with respect ION and IOFF were chosen depending on the percentage of the factor effect on S/N ratio that indicates the relative power of factor to reduce variation. The most dominant or significant factors in S/N Ratio are pocket halo implant dose and S/D implant energy. Meanwhile, the values of ION and IOFF values for 19nm WSi2/SiO2 NMOS device after optimization approaches are 591.38 µA/µm and 2.217 pA/µm respectively. The results obtained are meet the requirement of International Technology Roadmap Semiconductor (ITRS) 2013 prediction.